Impact of Accounting Variables on Stock Price of Nepalese Commercial Banks - Aryal, Sagar Babu; Gupta, Saloni; Giri, Sapna; Mahato, Shrijana; Rokaya, Shyam Bahadur; Pradhan, Radhe Shyam (Nepalese Journal of Finance, 2025)
The study examines the effect of accounting variables on stock prices of Nepalese commercial banks. The dependent variables selected for the study are market price per share and market capitalization. The selected independent variables are dividend per share, earnings per share, book value per share, return on assets, return on equity and net income. The study is based on secondary data of 11 commercial banks with 103 observations for the study period from 2013/14 to 2022/23. The data were collected from Banking and Financial Statistics published by Nepal Rastra Bank and annual reports of the selected commercial banks and NEPSE. The correlation coefficients and regression models are estimated to test the significance and importance of accounting variables on stock prices of Nepalese commercial banks. The study showed that earnings per share has a positive effect on market price per share and market capitalization. It means that increase in earnings per share leads to increase in market price per share and market capitalization. Similarly, dividend per share has a positive effect on market price per share and market capitalization. It means that increase in dividend per share leads to increase in market price per share and market capitalization. The results of the study also showed that book value per share has a positive effect on market price per share and market capitalization. It implies that increase in book value per share leads to increase in market price per share and market capitalization. Likewise, return on equity has a positive effect on market price per share which indicates that higher return on equity leads to increase in market price per share. However, net income has a negative effect on market price per share. It implies that higher net income leads to decrease in market price per share.